Investigating the Hepatoprotective Properties of Rutin Against Oxidative Stress and Liver Injury Induced by Paclitaxel in Rats - Jasim, Mohammed Maseer; Neamah, Nadheerah F; Ghanem , Waleed Khaled (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Liver toxicity remains a critical adverse effect of many chemotherapeutic agents, significantly limiting their clinical utility. Specific Background: Paclitaxel, a potent anticancer drug, is known to induce hepatic injury through oxidative stress, inflammation, and apoptosis. However, effective strategies to prevent such hepatotoxicity are limited. Knowledge Gap: While rutin, a natural flavonoid, exhibits antioxidant and anti-inflammatory effects, its protective role against paclitaxel-induced liver injury has not been fully elucidated in vivo. Aims: This study aimed to investigate the hepatoprotective potential of rutin against paclitaxel-induced hepatic damage in male rats through biochemical, oxidative, and histopathological assessments. Results: Rutin administration markedly reduced serum ALT, AST, and MDA levels while increasing GPx activity, restoring hepatic architecture, and alleviating necrosis, sinusoidal congestion, and apoptosis compared with paclitaxel-only groups. Novelty: This study provides novel experimental evidence demonstrating that rutin counteracts chemotherapy-induced hepatotoxicity primarily via antioxidant, anti-inflammatory, and anti-apoptotic mechanisms. Implications: The findings suggest that rutin could serve as a promising adjunctive therapy to protect against drug-induced liver injury in cancer patients undergoing paclitaxel treatment, warranting further clinical evaluation.Highlight : Rutin reduced oxidative stress and normalized liver enzymes in paclitaxel-treated rats. Co-administration of rutin preserved hepatic structure and improved antioxidant status. Rutin showed hepatoprotective effects against paclitaxel-induced liver injury. Keywords : Rutin, Paclitaxel, MDA, GPx, ALT, AST